Human capital development in Belarus via in-house investment - Makovskaya, Nataliya (Information & Media, 2016)
The subject of this research is the process of organising in-house training of employees and the efficiency of in-house investment in its framework. The purpose of the study is to determine the specificity of the organisation of in-house training in order to increase the efficiency of in-house investment of human capital resources in Belarus. The article presents a comparative analysis of approaches to the organisation of in-house training of employees in Russia and Belarus. The analysis was performed in the directions of identity assess the structure, objectives, principles and objectives of the in-house training of staff. It is possible to reveal the specifics of the institutional features and in-house training of employees in enterprises of Russia and Belarus, to evaluate innovative tools of in-house training for different categories of staff, taking into account the age and length of service.
Keywords: in-house training; human capital investment; employee; employer; efficiency of economic activities; the effectiveness of investment